Multiple Choice Questions in Medical Education: How to Construct High Quality Questions - Salam, Abdus; Yousuf, Rabeya; Bakar, Sheikh Muhammad Abu (International Journal of Human and Health Sciences (IJHHS), 2020)
Multiple choice questions (MCQ) are the most widely used objective test items. Students often learn what we assess, and not what we teach, although teaching and assessment are the two sides of the same coin. So, assessment in medical education is very important to ensure that qualified competent doctors are being produced.A good test is the test that assesses higher level of thinking skills. Many inhouse MCQs are found faulty which assess lower level of thinking skills. The main problems in constructing good MCQs are that (i) very few faculty members have formal training in questions construction, (ii) most of the questions are prepared in the last minutes where little time exist for vetting to review the quality of questions and (iii) lack of promise on the standard of the question format and underestimation of the use of blueprint in medical schools. Constructing good MCQs, emphasis should be given that, the stem is meaningful and present a definite problem, it contains only relevant material and avoid negativity. It should be ensuring that, all options present as plausible, clear and concise, mutually exclusive, logical in order, free from clues and avoid ‘all of the above’ and ‘none of the above’. The MCQs can tests well any higher level of the cognitive domain, if it is constructed well. Efforts must be made to prepare and use of test blueprint as a guide to construct good MCQs. This paper describes and offers medical teachers a window to a comprehensive understanding of different types and aspects of MCQs and how to construct test blueprint and good MCQs that tests higher order thinking skills in the future medical graduates, thereby ensures competent doctors are being produced. International Journal of Human and Health Sciences Vol. 04 No. 02 April’20 Page : 79-88